Rational choice of itemized deductions - Matthias Wrede (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2013)
This paper analyzes the effect of standard deductions on itemized deductions. Using German income tax data, it shows that the distribution of itemized deductions above the level of the standard deduction is positively skewed, with the mode lying somewhat above the standard deduction. This pattern of claimed tax allowable expenses could be easily explained by the rational minimization of tax payments in excess of the costs of reporting these deductions. An alternative explanation, namely tax aversion, is unable to replicate this pattern, as tax aversion would predict bunching of taxpayers directly above the lump-sum deduction.
Keywords: H24; H26; 330; tax compliance; tax allowable expenses; itemized deductions; simplification